PENGARUH FLYPAPER EFFECT PADA DANA ALOKASI UMUM (DAU) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA DAERAH PEMERINTAH KOTA SURABAYA (STUDI KASUS PERIODE 2011-2017) - Firdayanti, Febriana; Hidayat, M. Taufiq (Universitas 17 Agustus 1945 Surabaya, 2019)
ABSTRACTThe picture of regional independence in the era of autonomy is reflected in the ability of regions in the field of financial resources. Regional Original Income (PAD) should be the main financial source of the Regional Government. However, the increase in central government transfers, especially the general allocation fund (DAU), triggered spending that was greater than the increase in PAD. This condition is called the flypaper effect phenomenon. This study aims to analyze the effect of General Allocation Funds and Regional Original Revenues on Regional Expenditures and then analyze the Flypaper effect. This type of research is quantitative research. The population in this study is the Surabaya City Government. Determination of the sample uses sampling techniques with saturated sampling, where all members of the population are used as samples of the 2011-2017 Budget Realization Report. Data collected is secondary data with documentation method. The data analysis technique uses multiple linear regression analysis. The results of this study indicate that the General Allocation Fund variable in a persial manner does not have a significant effect on Regional Expenditures as evidenced by the results of a significantly greater value (0.914> 0.05), whereas Regional Original Revenues significantly influence Regional Expenditure as evidenced by a significantly smaller value level (0,000 <0,05). Simultaneously General Allocation Funds and Regional Original Revenues have a significant effect on Regional Expenditures as evidenced by a significantly smaller value level (0,000 <0,05). The results of this study identify that the effect of Regional Original Income on Regional Expenditure is greater than the effect of the General Allocation Fund on Regional Expenditures as evidenced by the PAD value of Regional Expenditures of 0.985 greater than the DAU coefficient of Regional Expenditures of 0.011. Therefore, in this study it can be concluded, there is no effect paper on the Regional Expenditures of the Surabaya City Government. Keywords: General Allocation Funds (DAU), Regional Original Revenue (PAD), Regional Expenditures, Flypaper effect